Factors affecting the oxidation behaviour of thin Fe-Cr-Al foils. Part II: The effect of alloying elements: Overdoping - Klöwer, J. (Materials and corrosion, 2000)
The oxidation behaviour of iron‐chromium‐aluminium alloys containing 7 mass‐% aluminium, additions of silicon and reactive elements (Hf, Y, Ti, Ce, La, Zr) was investigated at temperatures ranging between 900 and 1300°C. It was found that a significant increase in the oxidation rate and in the depth of internal oxidation (so‐called “overdoping”) occurs above a critical concentration of reactive elements. The critical upper limit of each reactive elements depends on the aluminium concentration, on the kind of the respective reactive element and on the type and amount of other reactive elements. Alloys containing yttrium are only subject to internal oxidation at yttrium concentrations of 0.08 mass‐% and more. The susceptibility to “overdoping” is significantly increased by additions of zirconium and titanium to yttrium‐containing alloys. Additions of hafnium, on the other hand, decrease the oxidation rate and the susceptibility to overdoping. Zum Oxidationsverhalten dünner Fe‐Cr‐Al‐Folien. Teil II: Der Einfluss von Legierungselementen: “Overdoping” Das Oxidationsverhalten von Eisen‐Chrom‐Aluminiumlegierungen mit 7 Masse‐% Aluminium, sowie Zusätzen von Silizium und reaktiven Elementen (Hf, Y, Ti, Ce, La, Zr) wurde im Temperaturbereich zwischen 900 und 1300°C untersucht. Es zeigte sich, daß reaktive Elemente oberhalb einer kritischen Konzentration einen starken Anstieg der Oxidationsgeschwindigkeit und eine innere Oxidation (sogenanntes „Overdoping“) bewirken. Die kritische Obergrenze hängt vom Aluminiumgehalt, von der Art des jeweiligen reaktiven Elementes und von der Art und Konzentration anderer reaktiver Elemente ab. Legierungen mit Yttrium zeigen Overdoping erst bei einer Konzentration von mehr als 0,08 Masse‐%. Die Neigung zum „Overdoping“ wird jedoch signifikant erhöht, wenn yttriumhaltigen Legierungen Titan oder Zirkon zulegiert wird. Auf der anderen Seite bewirken Zusätze von Hafnium eine Abnahme der Oxidationsrate und der Empfindlichkeit gegenüber „Overdoping“.